A study of relationship between perceived stress, coping pattern, burnout, and general psychopathology among the postgraduate medical students - K V Guruprakash; S G Mehta; Bajpai Atul; Jyoti Prakash; K J Divinakumar; S A Khan; P Patra (Industrial Psychiatry Journal, 2018)
Introduction: Medical postgraduate student experience considerable stress during their training, which may cause agony to the individual or affect care rendered to the patient. Significant burnout and psychopathology has not been uncommon. Materials and Methods: A study was done to assess the relation between perceived stress, coping pattern, burnout, and general psychopathology among the postgraduate medical students. Results: Perceived stress was associated with higher scores on general psychopathology and burnout. Postgraduate students who displayed positive coping strategies had lesser perceived stress. Females had higher scores on perceived stress and psychopathology. Conclusion: Stress is one of the major growing mental problems among highly educated health professional, and it should not be ignored as it can cause many other health issues.